Ending "Too Big To Fail": Government Promises versus Investor Perceptions - Todd A. Gormley; Simon Johnson; Changyong Rhee (Asian Development Bank (ADB), 2012)
Can a government credibly promise not to bailout firms whose failure would have major negative systemic consequences? Our analysis of the Republic of Korea's 1997–1999 crisis, suggests an answer: No. Despite a general "no bailout" policy during the crisis, the largest Korean corporate groups (chaebol)1em1ptfacing severe financial and governance problems1em1ptcould still borrow heavily from households through issuing bonds at prices implying very low expected default risk. The evidence suggests "too big to fail" beliefs were not eliminated by government promises, presumably because investors believed that this policy was not time consistent. Subsequent government handling of potential and actual defaults by Daewoo and Hyundai confirmed the market view that creditors would be protected.
hdl:11540/1272
Keywords: 330; Wirtschaftskrise; Unternehmenserfolg; Öffentliche Ausgaben; Schuldenübernahme; Liquiditätsbeschränkung; Südkorea